Characteristics of Inceptisol Soil in Latuhalat Village, Ambon City - Riry, Roberth Berthy; Tetelepta, Edward Gland (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Soil formation is the result of interactions between various processes, including geomorphological and pedological processes, where the soil body must be seen as a dynamic medium. Soil development is determined by soil formation factors, namely climate, topography, organisms, parent material, and time. In the process of soil formation, soil formation factors interact in the form of physical, chemical, and biological processes. The physical properties of the soil consist of soil color, soil texture, soil structure, soil consistency, soil pores, aggregates, coarse materials, mineral modules, and root conditions. The chemical properties of the soil include Base Saturation (BS), Cation Exchange Capacity (CEC), pH, Organic Carbon, and CaCO3 content. Meanwhile, the biological aspect of the soil consists of organism activities within the soil. The purpose of this study is: 1) to classify soil properties or group soils into specific classes based on their similar characteristics and features, including physical, chemical, and biological properties in the field; 2) to determine the soil type names based on the Technical Guidelines for National Soil Classification (BP3KP, 2014) and Soil Taxonomy Classification (USDA 2015) criteria. The method used is a survey method with a transect approach pattern and observation of pit profile types. The research results indicate that the soil type formed in the research location according to the criteria of the Technical Guidelines for National Soil Classification (BP3KP, 2014) is the Kambisol soil type. Approaching the Soil Taxonomy Classification (USDA 2015), this soil is included in the Inceptisol order, Tropept suborder, and Dystropept Great Group.